Materialism and Consumer Behavior: Differences in Types of Materialism Among Different Cultures - Moore, Kelvyn A.; Berger, Paul D. (Indian Journal of Marketing, 2015)
This research paper sought to ascertain the importance of values among different groups of individuals, differentiated by gender, age, and ethnicity. The paper contributes to understanding materialism among different cultures. It provides a broader perspective on how those living in one very strong materialistic culture are more vs. less materialistic. A social influence perspective is applied. The paper also provided a broader perspective on materialism, by considering all cultures in a metropolitan area that is composed of a melting pot of cultures. While one research survey mechanism was used to identify a variety of elements that are related to individual materialism, this research incorporated not only one reliable research measure tool from the past, but also a more recently developed and validated research measure. Findings suggest that attitudes toward materialism directly affect consumer behavior and thus, marketing strategy.